Being objective as being related. Some notes to the contribution of Paolo Bellan, starting from reading of Francesco Emmolo’s and Carlo Sini’s essays (18/05/2013) (Nóema, 2013)
The article is the consequence of some critical notes to the contribution of Paolo Bellan, arising from reading of essays of Francesco Emmolo and Carlo Sini and the assumption of a purely phenomenological perspective in the interpretation of the processes of acquisition of scientific knowledge.
Keywords: Husserl; crisis of sciences; subjectivity; Hermeneutics of science; Einstein; Relativity Theory; World of Life; Phenomenological theory of knowledge